DEVELOPING AUGMENTED REALITY-BASED COMICS IN IMPROVING COMPUTATIONAL THINKING AND NUMERACY FOR ELEMENTARY SCHOOL STUDENTS - Fatimatuzzahro; Fery Muhamad Firdaus (Universitas Muhammadiyah Bengkulu, 2025)
This research aimed to produce augmented reality-based comics to determine the effectiveness, the worthiness, and the practicality of the comics produced in improving computational thinking and numeracy skill for fifth grade elementary school students. This research and development were carried out referring to the steps developed by Borg and Gali. Thus, indicatingthat a statement items were valid. Reliability test showed that the variables were reliable, with Cronbachs Alpha values exceeding 0,60. Reliability test for Computatinal thinking and numeracy showed reliability, with a Cronbachs Alpha value of 0,762>0,60. Data Analysis techniques included preliminary test such as normality test, homogeneity test, independent sample t-test hypothesis test and efective relative. The results of the research are as follows: (1) augmented reality-based comics according to the assessment of material experts and media experts is very worthy of being tested in research to improve students' computational thinking and numeracy skills. (2) augmented reality-based comics as media with a significance value of 0.00< 0,05. The Average pretest score for Computational Thinking and Numerasy is 48,66, while in the control class, it is 49,56. The average posttest score for Computational Thinking and Numerasy in the experimental class is 74,29, whereas, in the control class, it is 65,46. (3) Augmented reality-based comics obtained significant results in improving students' computational thinking and numeracy skills, based on the results of the t-test of post-test with a significance value of 0.00<0.05 students before and after using augmented reality-based comics. Keywords: media, comics, augmented reality, computational thinking, numeracy